A comparison of various approaches used in source apportionments for precipitation nitrogen in a mountain region of southwest China. (October 2018) - Cui, Jian; Zhou, Fengwu; Gao, Min; Zhang, Liuyi; Zhang, Leiming; Du, Ke; Leng, Qiangmei; Zhang, Yuanzhu; He, Dongyi; Yang, Fumo; Chan, Andy
Abstract: Six different approaches are applied in the present study to apportion the sources of precipitation nitrogen making use of precipitation data of dissolved inorganic nitrogen (DIN, including NO3 − and NH4 + ), dissolved organic nitrogen (DON) and δ 15 N signatures of DIN collected at six sampling sites in the mountain region of Southwest China. These approaches include one quantitative approach running a Bayesian isotope mixing model (SIAR model) and five qualitative approaches based on in-situ survey (ISS), ratio of NH4 + /NO3 − (RN ), principal component analysis (PCA), canonical-correlation analysis (CCA) and stable isotope approach (SIA). Biomass burning, coal combustion and mobile exhausts in the mountain region are identified as major sources for precipitation DIN while biomass burning and volatilization sources such as animal husbandries are major ones for DON. SIAR model results suggest that mobile exhausts, biomass burning and coal combustion contributed 25.1 ± 14.0%, 26.0 ± 14.1% and 27.0 ± 12.6%, respectively, to NO3 − on the regional scale. Higher contributions of both biomass burning and coal combustion appeared at rural and urban sites with a significant difference between Houba (rural) and the wetland site (p < 0.05). The RN method fails to properly identify sources of DIN, the ISS and SIA approach only respectively identifies DON and DIN sources, the PCA only tracks source types for precipitation N, while the CCA identify sources of both DIN and DON in precipitation. SIAR quantified the contributions of major sources to precipitation NO3 − but failed for precipitation NH4 + and DON. It is recommended to use ISS and SIAR in combination with one or more approaches from PCA, CCA and SIA to apportion precipitation NO3 − sources. As for apportioning precipitation NH4 + sources, more knowledge is needed for local 15 N databases of NH3 and DON and 15 N fractional mechanisms among gaseous, liquid and particulate surfaces in this mountain region and similar environments. Graphical abstract: Highlights: Six source apportionment approaches were compared to each other. One approach played a quantitative role in the mountain region of Southwest China. Four approaches prevailed and gave qualitative sources, respectively. Combustion sources were dominated in precipitation DIN. DON mainly derives from volatilization sources such as animal husbandries.